Metal‐Organic‐Framework‐Derived Porous Carbon Embedded with TiO2 Nanoparticles as a Cathode for Advanced Lithium–Sulfur Batteries. Issue 1 (13th October 2020) - Qi, Chu; Li, Huilan; Wang, Jia; Zhao, Chengcheng; Fu, Cuimei; Wang, Lina; Liu, Tianxi
Abstract: The undesired internal shuttling of soluble polysulfide intermediates (Li2 Sn, 2<n≤8) remains the primary challenge hindering the development of lithium‐sulfur (Li−S) batteries. Engineering and functionalizing the cathode structure to trap Li2 Sn is a straightforward approach to address this issue. Metal‐organic framework (MOF)‐derived materials are applausive candidate host materials of sulfur, owing to the highly porous characteristic. In this work, a Ti−MOF‐derived micro‐sized cake‐like carbon skeleton with in situ generated hierarchical pores and anatase TiO2 crystalline grains is applied as an effective sulfur host in Li−S batteries. In this rational design, the pyrolytic porous carbon provides fast ion diffusion and physical confinement of polysulfides. The polar TiO2 affords abundant anchoring sites to achieve chemical encapsulation of sulfur species and accelerate polysulfide conversion kinetics. Benefiting from the fast reaction kinetics, the hybrid sulfur cathode delivers an elevated cycling performance with a capacity decay of only 0.39 % per cycle at 0.5 C (1 C=1675 mA g −1 ) over 100 cycles. In addition, an improved rate capability of 620 mAh g −1 at 2 °C is obtained. This work affords a facile method to design optimized cathodes towards advanced Li−S batteries. Abstract : MOF to a flame : This work demonstrates Ti‐metal‐organic‐framework (Ti−MOF)‐derived TiO2 /C skeletons with in situ generated hierarchical pores and TiO2 crystalline grains, which effectively encapsulate sulfur species and accelerate polysulfide conversion kinetics in lithium‐sulfur batteries.